TRANSFORMASI DIGITAL PROFESI HUKUM: PERAN DAN KONTRIBUSI PROFESI HUKUM PADA MASYARAKAT MODERN DI ERA DIGITALISASI - Muhammad Ilham Shiddiq; Abdullah Sathori (JURNAL ILMIAH NUSANTARA, 2025)
The legal profession is one of the most crucial jobs for human life. The legal profession is tasked with upholding the law by which the welfare, peace of human life and justice can be realized. Realizing this, it is certainly very important to understand how the legal profession is in this era of digitalization. Because there are so many jobs that have been affected by the presence of new technologies that are developing rapidly in this modern era, such as information and communication technology, AI and so on. If something cannot adapt to the improvement of the era, it will certainly be destroyed and abandoned as obsolete, in this case, it can cause the legal profession to no longer be trusted as a justice enforcer which will certainly have a fatal consequences. Therefore, it is important for us as the authors to examine this issue to find out what the legal profession is, and how to adapt to technological developments in this digitalization era. This research is a qualitative study which the data is collected with libraric research methods and then explained in a descriptive-analytic way. The results of this study indicate that the legal profession is indeed experiencing changes in the era of digitalization, this change can be felt from the existence of jobs that are replaced by digital machines which cause changes in the work portion of legal professionals. In addition, the digitalization of the legal profession also brings new challenges to improve the quality of work of legal professionals where a person in the legal profession is required to hone intelligence and conscience sensitivity because that is how justice can be maintained in this digitalization era.